The inherited mind : a story of family, hope, and the genetics of mental illness - Longman, James (Journalist) (Hyperion Avenue, 2025)
James Longman was a preteen in boarding school when his dad, who was diagnosed with depression and schizophrenia, died by suicide. As he got older, James's own bouts of depression spurred him to examine how his father's mental health might have affected his own. He engaged with experts to uncover the science behind what is inherited, how much environmental factors can impact genetic traits, and how one can overcome a familial history of mental illness and trauma.--